Management and Islamic Leadership in the Al-Washliyah Organization - Barani; Syafnan; Hasnah (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
Al-Jam’iyatul Washliyah is one of the Islamic organizations in Indonesia. The word Al-Jam’iyatul Washliyah comes from Arabic which means a gathering or association that connects. An Islamic group involved in community service, education, and da'wah (spiritual guidance), the Al-Wasliyah organization is the focus of this research. Qualitative methods, including in-depth interviews, observation, and documentation, make up the research strategy. The data was subjected to thematic analysis to reveal recurring themes regarding implementing Islamic leadership and management concepts. The results of the study show that Al-Wasliyah consistently applies Islamic values in its organizational activities, such as shura (deliberation), amanah (trust), justice, and management efficiency. Leadership in Al-Wasliyah is based on Islamic principles, including the characteristics of Siddiq (honest), tabligh (communicative), fathanah (intelligent), and amanah (trustworthy). Based on Islamic teachings, organizational leaders act as role models, motivators, and decision-makers. However, this study also found challenges, such as the lack of consistency in applying Islamic management principles at the branch level, limited competent human resources, and minimal use of technology to support organizational activities. The main supporting factors for organizational success include strong Islamic values, extensive networks, and the spirit of Islamic brotherhood. This study concludes that the application of Islamic management and leadership in Al-Wasliyah has a positive impact on organizational performance, although efforts are still needed to modernize and strengthen in several aspects. Recommendations include increasing leaders' capacity, strengthening organizational structures, and utilizing digital technology to support more effective organizational management.